REGIONAL CENTERS OF ENTREPRENEURIAL ACTIVITY AS A NEED FOR SUSTAINABLE DEVELOPMENT ECONOMY OF UKRAINE: Array - Dymchenko, O.; Shkurupiy, K. (Municipal economy of cities. Series: «Economy science», 2019)
The article reveals the obstacles hindering the development of entrepreneurship in Ukraine, analyzes information on specific aspects of entrepreneurship in Ukraine. Experience and macroeconomic indicators of European Union countries are analyzed. Today, entrepreneurship is very important for Ukraine. Enterprises provide sustainability and development of the economic system in the country, meet the needs of consumers in various fields of activity, solve the problem of unemployment in the country and contribute to the further development of a large number of leading industries. The key to the rapid growth of our country’s economy is the creation of a Regional Center of Entrepreneurial Activity in each regional center of Ukraine, whose main purpose is to ensure sustainable development of entrepreneurship in Ukraine, by providing assistance to business development, providing consultations and practical services, such as: registration of business subjects, providing advice on issues of interest to entrepreneurs, finding partners and sponsors for businesses, creating educational platform for entrepreneurs, promoting the development of business entities, providing practical assistance to businesses in need, creating the right conditions for business development, arranging the delivery of documents from the Regional Center of Entrepreneurial Activity to the executive bodies involved in the provision of relevant services, delivery of source documents to the Regional Center of Entrepreneurial Activity involving representatives of the executive bodies of the council to resolve controversial issues that arise in the process. Aspects of functioning of the Center and further prospects of development are considered in detail.